STRUCTURE AND PREDICTORS OF COGNITIVE CHANGE IN THE EIGHTH DECADE OF LIFE - Ritchie, S. (Innov Aging, 2017)
‘Does it all go together when it goes?’ In this study, we addressed this classic question about whether cognitive abilities change together in later life. In detailed longitudinal cognitive testing data from the Lothian Birth Cohort 1936 study (initial n = 1,091), we factor-analysed the aging of thirteen different tests taken at ages 70, 73, and 76 years. We found evidence for a general factor of cognitive ageing explaining around 50% of the variation in change: individuals who declined more in one ability tended to decline in all of them. Next, we tested for predictors of this general cognitive aging process. From a wide variety of potential predictors—including genetic, health, lifestyle, and socioeconomic variables—we found that physical fitness and possession of the APOE e4 allele were the most promising predictors of the general cognitive ageing process.